Synergistic effect of Chaihu-Shugan-San combined with paroxetine tablets in the treatment of acquired premature ejaculation: study protocol for a randomized controlled proof-of-concept trial - Qian, Shengqiang; Wei, Jintao; Zhang, Peihai; Ma, Ziyang; Guo, Yu; Ren, Feiqiang; Xiong, Wei (Frontiers in Pharmacology, 2025)
IntroductionAcquired premature ejaculation (APE) is a common male sexual dysfunction characterized by a clinically significant reduction in intravaginal ejaculatory latency time. In China, its prevalence ranges from 4% to 39%, while globally, approximately 26% of men report premature ejaculation (PE), with APE accounting for 18.8% of cases. The mechanisms of APE remain unclear, with psychological factors (e.g., anxiety, depression) and neurological factors identified as key influences. Selective serotonin reuptake inhibitors (SSRIs), such as paroxetine, delay ejaculation by elevating synaptic 5-HT levels, but they are associated with side effects and poor compliance. Chaihu-Shugan-San (CHSGS), a classical Traditional Chinese Medicine (TCM) formula for depression and anxiety, is commonly used in TCM andrology for APE. It is hypothesized that CHSGS alleviates APE symptoms by improving emotional states through central nervous system modulation.Methods and analysisThis is a randomized, blinded interventional trial with four parallel groups. A total of 84 eligible participants will be randomly assigned to one of four groups: the paroxetine group, CHSGS group, CHSGS + paroxetine group, or placebo group. The primary outcomes are Intravaginal ejaculatory latency time (IELT) and Pre- and post-treatment brain fMRI scans. The Secondary Outcomes include Premature ejaculation profile (PEP), Chinese Index of Premature Ejaculation (CIPE) and TCM syndrome score.Ethics and disseminationThe trial has been registered with the International Traditional Medicine Clinical Trial Registry (Registration No. ITMCTR2025000309) and Ethics Committee of Chongqing Hospital of Traditional Chinese Medicine (Registration No. 2023-ky-87). It will be proceeded in the Departments of Urology and Radiology at Chongqing Traditional Chinese Medicine Hospital in Chongqing, China.Trial registration numberITMCTR2025000309.